La enseñanza de la matemática a través de la actividad lúdica para fortalecer la habilidad lógica matemática en los estudiantes del tercer año de educación general básica del centro educativo “Rafael Cajiao Enríquez” de la parroquia de Pastocalle, barrio Cuilche Miño, durante el año lectivo 2012-2013. - Cajamarca Lema, Sorayda Magaly (2014)
Due to the motivation lack for the math study that was have looked today since it makes of the class a presentation of the issues than a meaningful learning, it is indispensable to know and apply techniques that allow what the students math thinking will be an applicable process to their daily live. The leisure activity insufficient to the hour of performing the math class makes that the education back in the time, transforming in a traditionalist activity; even more, it is being knower that currently, there are methods series to help what children have a good math reasoning. The math activity had had since always a playful component which the same teaching; the teachers should will always applied this technique as it is intimately related of achieving the better results in the education. The implementation and application of the leisure activities in the math teaching exclusively through recreational games will strengthen the logical skill math in the children; its turn will allow working in an active, nice and participative environment.